2021
DOI: 10.1155/2021/2612441
|View full text |Cite
|
Sign up to set email alerts
|

Crack Group Effect Analysis of the Stress-Release Boot of Solid Rocket Motor Based on Numerical Simulation

Abstract: Due to the complex process of the insulation layer patch in solid rocket motor (SRM), only manual patch could be used. Sometimes weak bonding or debonding in each joint surface was inevitable. This study is aimed at determining the crack group effect of insulation and interfacial debonded crack in the wide-temperature SRM. The crack group appeared in the front area of the ahead stress-release boot and was induced by low temperature, axial overload, or interface bonding failure. Based on the viscoelastic finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In this paper, the stress-release boot of SRM under vertical storage has been optimized. Stress-release boot can effectively improve the structural integrity of the SRM under solidification load [12,13]. Zhang et al [14] analyzed the influence of the stress-release boot by numerical calculation and found that the maximum Von Mises strain of grain decreased from 30.1% to 23.0%.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the stress-release boot of SRM under vertical storage has been optimized. Stress-release boot can effectively improve the structural integrity of the SRM under solidification load [12,13]. Zhang et al [14] analyzed the influence of the stress-release boot by numerical calculation and found that the maximum Von Mises strain of grain decreased from 30.1% to 23.0%.…”
Section: Introductionmentioning
confidence: 99%